Damage, Loss, and Needs Assessment Guidance Notes : Volume 2. Conducting Damage and Loss Assessments after Disasters - Jovel, Roberto J.; Mudahar, Mohinder (World Bank, Washington, DC, 2014)
This is a guideline for World Bank task team leaders (TTLs) entrusted with the design and execution of assessments to determine disaster impacts as well as post-disaster needs for recovery, reconstruction, and disaster risk reduction or management. Assessments estimate, first, the short-term government interventions required to initiate recovery and second, the financial requirements to achieve overall post-disaster recovery, reconstruction, and disaster risk management or reduction. The end product of the assessment is a comprehensive program of recovery, reconstruction, and risk management that will guide all actions in a developing country following a disaster. The damage and loss assessment (DaLA) methodology uses objective, quantitative information on the value of destroyed assets and temporary production losses to estimate, first, government interventions for the short term and second, post-disaster financing needs. The DaLA method ensures that the affected government, the United Nations and other international and domestic agencies jointly develop properly estimated and prioritized financial requirements and an accompanying formula that identifies all possible financial sources and modalities. In addition, the estimation of the needs can be used as a basis to monitor post-disaster recovery and reconstruction progress. The DaLA aim at operationalizing the concepts for practitioners at government agencies, the World Bank, and other national and international organizations, responsible for assessing the impact of disasters, and for developing recovery and reconstruction plans. The guidance notes comprises of three volumes: (i) guideline for TTL in the design and execution of a damage, loss, and needs assessment, (ii) conducting damage and loss assessments after disasters, and (iii) estimation of post-disaster needs for recovery and reconstruction.